Implementasi Kebijakan Penyaluran Pupuk Bersubsidi Dalam Upaya Peningkatan Produksi Padi di Subak Kabupaten Bangli - Sriwulandari, Komang; Wirantari, I Dewa Ayu Putri; Prabawati, Ni Putu Anik (Socio-political Communication and Policy Review, 2024)
The agricultural sector is an important sector in providing food and has a direct impact on the basic needs of the Indonesian people. The role of farmers and government is needed to increase the amount of rice production. Increasing the amount of rice production by farmers is carried out by continuing to plant rice and increasing the amount of rice production. Due to this, the government issued a policy of distributing subsidized fertilizer in an effort to help farmers increase rice production. Bangli Regency is a district that has land that has the potential to produce rice. In this regard, in efforts to implement the subsidized fertilizer distribution policy, the Department of Agriculture, Food Security and Fisheries of Bangli Regency has the task of assisting farmers in efforts to increase rice production. The purpose of this research is to find out how the Subsidized Fertilizer Distribution Policy is implemented in an effort to increase rice production in Subak, Bangli Regency, using qualitative methods and using research indicators proposed by George C. Edwards III (2009), namely communication, resources, disposition and bureaucratic structure. The results of this research show that communication, resources, disposition and bureaucratic structure are still not running optimally. Thus, the Department of Agriculture, Food Security and Fisheries of Bangli Regency needs to make improvements to each indicator. extension and improving the scheduling of extension and assistance to farmers.